2010
DOI: 10.1128/jvi.00463-10
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sensitivity of Well-Differentiated Avian Respiratory Epithelial Cells to Infection by Different Strains of Infectious Bronchitis Virus

Abstract: Infectious bronchitis virus (IBV) is an avian coronavirus affecting the respiratory tract of chickens. To analyze IBV infection of the lower respiratory tract, we applied a technique that uses precision-cut lung slices (PCLSs). This method allows infection of bronchial cells within their natural tissue composition under in vitroconditions. We demonstrate that IBV strains 4/91, Italy02, and QX infect ciliated and mucus-producing cells of the bronchial epithelium, whereas cells of the parabronchial tissue are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 8 publications
(14 reference statements)
1
23
0
Order By: Relevance
“…Pretreatment with neuraminidase was found to result in decreased infectivity as indicated by a reduced number of infected cells and by lower titers of virus released into the supernatant. This finding was obtained with both a lab strain and strains circulating in poultry [124][125][126]. The sialic acid-dependence of the IBV infection was observed both with conventional cell cultures and differentiated airway epithelial cells from trachea and lung [126,127].…”
Section: Gammacoronavirusesmentioning
confidence: 61%
“…Pretreatment with neuraminidase was found to result in decreased infectivity as indicated by a reduced number of infected cells and by lower titers of virus released into the supernatant. This finding was obtained with both a lab strain and strains circulating in poultry [124][125][126]. The sialic acid-dependence of the IBV infection was observed both with conventional cell cultures and differentiated airway epithelial cells from trachea and lung [126,127].…”
Section: Gammacoronavirusesmentioning
confidence: 61%
“…Reports about infection studies with PCLS are rare and restricted to the murine, bovine, and avian lungs [10], [11], [17], [18]. In this study, PCLS prepared from porcine lungs were shown to be a valuable culture system for porcine differentiated respiratory epithelial cells.…”
Section: Discussionmentioning
confidence: 79%
“…For human work, ALI cultures are an alternative if the tissue samples are limited, but human lung slices can be commonly obtained from surgical specimens and have been used to examine infection with adenovirus type 7 [103] or with anthrax spores [104]. Avian lung slices infected with infectious bronchitis virus for a week displayed an infection pattern based on strain and innoculum dose [105]. This distribution appeared to match the distribution or expression of the sialic-acid based receptor sites, detected with lectin, on the epithelial cells and used by the virus for infection.…”
Section: Pathophysiology In Lung Slicesmentioning
confidence: 99%